PELATIHAN OPTIMALISASI PEMBAYARAN DENGAN MENGGUNAKAN APLIKASI UNTUK MENINGKATKAN EFESIENSI PADA UMKM - Amanda, Azhara Yunefa; Fatichah, Zuchriyah; Wahyu Nazila; Zara Tania Rahmadi; Dias Adi Dharma (ASOSIASI IDEBAHASA KEPRI, 2025)
The Small and Medium Enterprises (SMEs) sector plays a crucial role in Indonesia's economy, contributing over 60% to the GDP and significantly aiding in job creation. However, many SMEs face challenges in adopting technology, particularly in digital payment systems. This study explores the potential of optimizing digital payment methods to improve operational efficiency in SMEs. The research focuses on providing training for SMEs, particularly in the culinary industry, to help them transition from traditional cash payments to digital transactions. Using a hands-on training approach, the study demonstrates how SMEs can integrate digital payment applications into their operations, resulting in increased efficiency, better financial record-keeping, and enhanced customer satisfaction. The findings underscore the importance of digital payment adoption for enhancing business competitiveness and customer convenience in a rapidly evolving digital landscape. Ultimately, this initiative shows that training SMEs in digital payments can drive substantial operational improvements and prepare them for a more competitive market environment.